2010
DOI: 10.1007/s10646-010-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards clarification of the inhibitory mechanism of wheat bran leachate on Microcystis aeruginosa NIES-843 (cyanobacteria): physiological responses

Abstract: Wheat bran leachate (WBL) has been shown to have an inhibitory effect on Microcystis aeruginosa in this study. In order to explore the inhibitory mechanism of WBL on M. aeruginosa, physiological responses of M. aeruginosa NIES-843 under the WBL stress were studied. The expressions of six important genes related to the D1 protein of photosynthetic processes (psbA), synthesis of microcystins (mcyB), antioxidant protein peroxiredoxin (prx), synthesis of fatty acid (fabZ) and the repair of biological macromolecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Activities of respiration and photosynthesis could reflect the vitality of microorganisms [ 25 , 26 ]. The respiration rate of YYLX235 in the acidified treatments (pH 6.0–4.0) was far lower than the neutral control, indicating that the acidification of paddy floodwater decreased cell vitality of this diazotrophic cyanobacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of respiration and photosynthesis could reflect the vitality of microorganisms [ 25 , 26 ]. The respiration rate of YYLX235 in the acidified treatments (pH 6.0–4.0) was far lower than the neutral control, indicating that the acidification of paddy floodwater decreased cell vitality of this diazotrophic cyanobacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Allelochemicals such as lysine, Some allelochemicals show only weak inhibitory effects on cyanobacteria. For example, bionone is an antialgal compound that inhibits Microcystis, but the EC50 is 22 mg/L [212]. Cyanobacteria can adapt to the inhibitory effect of some biologically derived substances (BDS) and become resistant to them.…”
Section: Disadvantages Of Plantsmentioning
confidence: 99%
“…Most of the microbial algae control technologies developed to date rely on algae-lysing bacteria [ 6 , 7 , 8 ], and the existing studies [ 9 , 10 , 11 ] have indicated that the Phanerochaete chrysosporium which control algae may be great in promoting the control of eutrophication by microbial methods. With the development of molecular biology, the molecular mechanism of the life activities of cyanobacteria and Microcystis aeruginosa has attracted people’s attention [ 12 , 13 , 14 , 15 ]. In recent years, the mechanisms involved in synthesizing various substances in M. aeruginosa cells [ 16 , 17 ], especially the molecular mechanisms that inhibit the growth of M. aeruginosa , have focused on biological rhythms, toxin synthesis, phycobiliprotein synthesis and its regulation, ATP synthetase [ 18 , 19 , 20 , 21 ], and the molecular response mechanisms through which algae removal technology affects the life activities of cyanobacteria, such as the regulation and expression of biorhythms and the regulation of algal toxin synthesis, have attracted increasing attention [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%